Potensi Aktivitas Antimalaria Residu Hidrodestilasi Kulit Kayu Manis (Cinnamomum Burmanii) Melalui Penghambatan Polimerisasi Heme - Dona, Rahma; Almurdani , M; Rivan , M; Ibad, M Zainul; Syafitri, Ikke Juwita; Azizah, Wahyu; Nur, Siti Rahmatun; Lestari, Putri (Jurnal Riset Kimia, 2024)
Cinnamon (Cinnamomum burmanii) is a herbal plant from Indonesia which is widely used in cooking, cosmetics and medicine. Cinnamon bark isolate is thought to contain compounds with the structure of isoquinoline which are known to be used as antimalarials. The aim of this study was to examine the potential antimalarial activity of extracts and fractions of cinnamon bark hydrodistillation residue based on the % inhibition and IC50 value. These results will also be compared with extracts and fractions of cinnamon bark without hydrodistillation as controls. The test method is carried out in vitro by heme polymerization inhibitor. The test results showed that the n-hexane fraction, DCM fraction did not have inhibitory activity, while the ethyl acetate fraction had better potential than other extracts and fractions, where the ethyl acetate fraction after hydrodistillation (residue) had an IC50 value of 71.84 µg/mL, while the ethyl acetate fraction without hydrodistillation (control) had an IC50 value of 120.05 µg/mL. This result is better than hydroxychloroquine as positive control which has an IC50 value of 184.98 µg/mL. These results indicate that the ethyl acetate fraction from the hydrodistillation residue of cinnamon bark can be utilized and has potential as an antimalarial.